Simulation of micro-optical systems including microlens arrays - Lindlein, Norbert (Journal of Optics A-Pure and Applied Optics, 2002)
The simulation of micro-optical systems, especially those including microlens arrays, is still a challenging task. There are of course traditional methods which can be applied under certain circumstances. This paper will discuss several geometrical optical and diffraction-based methods for the simulation of micro-optical systems. A simple paraxial geometrical optical matrix theory will be extended to the simulation of off-axis optical elements. Ray tracing will be used to model incoherent micro-optical systems. The propagation of Gaussian beams through off-axis optical systems using differential ray tracing will be discussed. The angular spectrum of plane waves will be used to propagate a scalar complex wave amplitude in free space simulating non-paraxial diffraction effects. Finally, a model will be proposed which combines ray tracing and wave propagation methods by converting a complex wave amplitude into rays and vice versa. In the case of wavefront warping a decomposition of the wave into elementary waves has to be performed. This combined model can take into account non-paraxial effects such as aberrations of optical elements and also diffraction effects.
UnivIS-Import:2015-03-09:Pub.2002.nat.dphy.optik.1optik.simula
Keywords: Optical system design; Wave propagation; Wavefronts and ray tracing